2014
DOI: 10.5551/jat.21790
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Alanine Aminotransferase(ALT), Visceral Adipose Tissue(AT) and Metabolic Risk Factors in a Middle-Aged Japanese Population

Abstract: Aim:The commonly observed relationship between increased visceral adiposity and metabolic abnormalities may be partly mediated by a concomitant increase in liver fat content. We evaluated the independent association between the level of alanine aminotransferase (ALT) as a surrogate marker of the liver fat content and the incidence of metabolic abnormalities after adjusting for the amount of visceral adipose tissue (AT). Methods: The subjects included 1,118 Japanese individuals (44% women) who underwent compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Although some previous studies only reported a remarkable association between ALT and hypertension in people with certain demographic characteristics [ 17 , 27 ], we found a similar association in subgroups, including BMI, HBsAg, sociodemographic characteristics (age, gender, and area) and health-related behaviors (alcohol drinking and cigarette smoking). Furthermore, interaction effects were also found between serum ALT levels and some conventional hypertensive risk factors.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although some previous studies only reported a remarkable association between ALT and hypertension in people with certain demographic characteristics [ 17 , 27 ], we found a similar association in subgroups, including BMI, HBsAg, sociodemographic characteristics (age, gender, and area) and health-related behaviors (alcohol drinking and cigarette smoking). Furthermore, interaction effects were also found between serum ALT levels and some conventional hypertensive risk factors.…”
Section: Discussionsupporting
confidence: 67%
“…Some studies revealed that plasma ALT was related to blood pressures (BP) [ 15 ], and the prevalence of hypertension was obviously increased with serum ALT levels [ 16 ]. Other studies did not reveal a substantial association between serum ALT and hypertension because of small sample size [ 13 , 17 ] or multiple metabolic confounding risk factors in research objects [ 17 ]. Meanwhile, a gender difference was found, the association between ALT and hypertension or BP levels was only discovered among males [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The serum E2 levels were similar in the two groups, however, the FSH levels were significantly increased in the peri-menopausal group. Furthermore, we adjusted the data by considering the effects of E2 and other confounders (e.g., age, BMI) using multivariate models 2,41 and ultimately found that the serum FSH levels were independently and positively correlated with the cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable linear regression model was used to analyze the association between FSH and cholesterol levels, with adjustment for estradiol levels and previously reported potential confounders. 2,41 Two-tailed P values less than 0.05 were considered statistically significant. The analyses were performed using SPSS version 22.0 for Windows (Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…ALT and AST are two key biomarkers of hepatic injury. An increased ALT/AST level is considered to reflect liver fat aggregation when alcohol consumption and viral hepatitis are excluded from the causes of fatty liver . These results indicated that the 5 week BBR‐CS/PT‐NPs treatment could successfully protect the HFD‐fed hamsters from hepatic steatosis and injury.…”
Section: Resultsmentioning
confidence: 91%